Biochemical Study on Anti Thyroid Peroxidase in Type 2 Diabetic patients with thyroid disorders (Baghdad Science Journal, 2025)
Type 2 diabetes mellitus (T2DM) is the most frequent endocrinal disease commonly associated with thyroid disorders .The study is conducted at the Specialized Center for Endocrinology and Diabetes in Baghdad ,during December 2014 up to October 2015.This study was done to investigate the prevalence of anti- thyroid peroxidase (Anti-TPO) antibody in patients suffered from type 2 diabetes with thyroid disorders .The study groups included a total number of 80 subjects consisting of 60 type 2 diabetic patients divided into 20 hyperthyroidism subjects (group 1) ,20 hypothyroidism subjects (group 2), 20 euthyroidism subjects (group 3) and 20 healthy controls (group 4) . The fasting blood samples were analyzed for (T3,T4,TSH) by using Vitek Immuno diagnstic Assay System (VIDAS). Enzyme Linked Immunosorbent Assay (ELISA) is used to detect anti-thyroid peroxidase (Anti-TPO) antibody .The results show that age, gender and BMI (body mass index) have significantly higher levels in the patients groups as compared to the healthy group at (p